Economic burden analysis of nosocomial infections in tertiary care hospital in western India: A prospective evidence-based study - Pranali Patil; Jignesh Shah; Amol Muthal; Asavari Raut (Clinical Epidemiology and Global Health)
Objective: To evaluate the costs associated with nosocomial infections in a tertiary care hospital in western India. Materials and methods: This prospective observational study was carried out in a 1000 bedded tertiary care teaching hospital with 100 bedded capacities of interdisciplinary ICUs for a period of 6 months. The costs of illness considered in the study included direct as well as indirect costs. Results: The most commonly occurring infection among the four categories of HAIs was ventilator-associated pneumonia (VAP) (54.16 %). The direct total costs associated with infected group (752,859 ± 92,233) was found to be significantly higher than uninfected group (290,500 ± 92,233) (p < 0.0001). The direct total costs incurred by VAP (803,605 ± 92,233) was found to be significantly higher followed by CAUTI, SSI and CRBSI. Similarly, the indirect cost was also found to be significant for VAP compared to other types of infections. It was observed that Length of ICU stay 0.997 (31,646–32,767) was significant factor which is responsible for the increase cost of treatment among patients with HAIs (p < 0.0001). Conclusion: The study highlights that hospital-acquired infections (HAIs) place a substantial financial strain on India's healthcare system. The findings emphasize the necessity for robust infection prevention strategies in hospitals to reduce the incidence of HAIs which could lead to significant cost savings and improved patient outcomes. Future studies could aim to calculate the full economic burden of HAIs, covering not only loss of productivity cost but also mortality and long-term morbidity costs.